The Influence of Self Development and Individual Competence on the Performance of Private Higher Education Managers : (By Intervening Organizational Climate and Controlled Behavioral Tendencies) - Rahyubi, Heri (EDUPEDIA Publisher, 2022)
Abstract: Private universities in the Kopertis IV area of ​​West Java and Banten for the Cirebon area face complex challenges and responsibilities, especially when it is associated with the national development expectations imposed on PTS towards a new Indonesian society. This study aims to determine the effect of self-development and individual competence on the performance of private university managers with organizational climate interventions and behavioral tendencies controlled. The type of research used in this research is the explanatory survey method. The population in this study were all managers of private higher education institutions Kopertis IV West Java and Banten for the Cirebon area, namely (1) Majalengka University, (2) Gunung Jati Swadaya University (UNSWAGATI), (3) Kuningan University and (4) Wiralodra University. . The sample used in this study was obtained by census from the population of this study which amounted to 159 people. An overview of the management practice of higher education in private universities in the Kopertis area IV West Java and Banten for the Cirebon area can be concluded that: (a) In general, the managers of private universities in the Kopertis area IV West Java and Banten for the Cirebon area are managed by people who have a tendency to STEJ behavior. (b) Self-development in four private universities in the Kopertis area IV West Java and Banten for the Cirebon area is classified as 'adequate' with a mean value of 3.92. Where most of the respondents view self-development as important. (c) Individual Competencies in four Private Universities in the Kopertis IV area of ​​West Java and Banten for the Cirebon area are classified as 'very adequate' with a mean value of 4.02. Where most of the respondents view individual competence as very important. (d) Organizational climate in four private universities in the Kopertis area IV, West Java and Banten for the Cirebon area is classified as 'conducive' with a mean value of 3.43. Where most of the respondents view organizational climate as important. (e) The performance of individual managers at four private universities in the Kopertis area IV, West Java and Banten for the Cirebon area is classified as 'adequate' with a mean value of 3.96. Where most of the individual performance of PTS managers is adequate.